Analysis of new retail business formats & Development Strategy Analysis of Yonghui Superstores new retail business - Lu, Xin Yao (2021)
This Master´s thesis is divided into two essential parts, the theoretical and practical part. In the first part, basic concepts related to some basic definitions will describe the individual analytical apparatuses used in this thesis. In the practical part, after the company and new retail business introduction, followed by a PEST analysis of micro-environment and industry analysis of Porter's five forces. Furthermore, evaluates the effective internal resources and summaries negative factors that affect the business. The results of SWOT analysis of YH including several competitive strengths that the possessed resource base of the company and its ability to effectively use it as well as some areas of weakness that can be improved, with the existence of numerous potential opportunities facing YH, and threats that prevent it from continuous development in supermarket retail industry. The thesis ends by proposing strategic recommendations that will be derived from the results of the strategic analysis.